Multimodality imaging in primary hyperparathyroidism. Issue 6 (June 2022) - Zarei, A.; Karthik, S.; Chowdhury, F.U.; Patel, C.N.; Scarsbrook, A.F.; Vaidyanathan, S.
Abstract : Institutional variations in parathyroid adenoma localisation are largely dictated by local experience and availability of imaging investigations, with no consensus on the optimal approach. This review evaluates the role of multiple imaging techniques in primary hyperparathyroidism and highlights their advantages and limitations in different clinical contexts. A clinico-radiological review of parathyroid imaging techniques is illustrated with example cases and data from the literature. These include high-resolution ultrasound, 99m Tc-sestamibi planar scintigraphy with and without thyroid subtraction techniques, integrated 99m Tc-sestamibi single-photon-emission computed tomography (SPECT)/computed tomography (CT), four-dimensional (4D) CT, and other techniques, such as magnetic resonance imaging, integrated 18 F-choline/ 11 C-methionine positron-emission tomography (PET)/CT and angiographic selective venous sampling. The crucial role of parathyroid embryological and gross anatomy in informing the surgical approach to parathyroidectomy is discussed. Finally, a systematic approach to imaging is proposed to maximise the accuracy of imaging localisation of parathyroid lesions, which is crucial for optimal patient management. Highlights: Primary hyperparathyroidism is most commonly caused by a solitary adenoma Surgery is curative and imaging plays a crucial role in localising candidate lesions The use of cross-sectional imaging in the form of either SPECT/CT or 4D-CT is superior to planar scintigraphy or ultrasound alone A multimodality imaging approach, combining ultrasound with either Sestamibi SPECT/CT or 4D-CT is synergistic and recommended first-line Other techniques such as Choline PET/CT and selective venous sampling are reserved for challenging (negative exploration) cases where available